Thermal Studies on Some Metal Polychelates - Rai, H.C.; Kumari, Poonam; Kumar, Ashwini; Chandra, Mrinal (Asian Journal of Chemistry, 2010)
Chelates of Mn(II), Fe(II), Co(II), Ni(II) and Cu(II) have been prepared with the Schiff base ligand derived from 4,4´-dihydroxy-3,3´ -diacetylbiphenyl and benzildihydrazone having equimolar stoichiometry of the metal cations and ligand. All the chelates are coloured amorphous solids and highly insoluble in water and common organic solvents. Thermogravimetric analyses have been cartied out. Kinetic and thermodynamic parameters have also been evaluated by using thermal decomposition pattern. D.C. electrical conductivity study has also been carried out. The ligand field and nephelauxetic parameters have also been determined from the spectra using ligand field theory of allowed transitions.